Eksistensi Kesenian Wayang Kulit Di Jorong Suka Bakti Solok Selatan - Adi Kurnia; Wimbrayardi Wimbrayardi (FBS Universitas Negeri Padang, 2021)
The purpose of this study was to describe the existence of Wayang Kulit art in Jorong Suka Bakti, South Solok Regency seen from the function and use of Wayang Kulit art in Javanese society in Jorong Suka Bakti. This type of research is qualitative research with a descriptive analysis method. The main instrument in this research is the researcher himself and is assisted by supporting instruments such as stationery and camera. Data collection techniques were carried out by literature study, observation, interviews, and documentation. The steps to analyze the data are collecting data, describing the data, and making conclusions. Puppet art in Jorong Suka Bakti is a traditional Javanese art that developed outside the area of origin of the Javanese people. The results and discussion in this article contain the use of Wayang Kulit art in the Javanese people of Jorong Suka Bakti in; village cleansing rituals; circumcision events; and wedding ceremonies. Wayang Kulit also functions as a vehicle for expression; social entertainment function; the function of the media that reflects the norms and aesthetic values as well as the economic function in supporting the necessities of life.